ANALISIS KETERAMPILAN MENGAJAR GURU TK YANG BERPENDIDIKAN S1 SE-KECAMATAN PAYUNG SEKAKI PEKANBARU - Sri Wahyu Ningsih; Zulkifli Zulkifli; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: The purpose of this study to determine the analysis of kindergarten teacher with bachelor’s of degree educated at Payung Sekaki district of Pekanbaru. Population and sample in this study were 22 people who had bachelor’s of degree educated at Payung Sekaki district of Pekanbaru. The data collection techniques that used was observation. Technique of data analysis was using a percentage formula. The results that obtained were teaching skills of kindergarten teacher at Payung Sekaki District of Pekanbaru overall was gain a percentage of 72.28% which is included in category of "Good". Based on the analysis of teachers' length of work, showing that length of work of teacher influence the teaching skills of kindergarten teacher at Payung Sekaki District of Pekanbaru. It can be known from the data analysis of the chi-square calculation that obtained result score of 41.187. This score compared with the chi-square value in the table with dk of 26 is at 5% significance level that is equal to 38.885, showing the results of calculation of chi square is greater than the chi square results in the table (41.866 > 38.855). Based on the analysis of taking the training, showing that training that teacher had took does not affect kindergarten teachers' teaching skills at Payung Sekaki District of Pekanbaru. It can be know from the data analysis of the chi-square calculation that obtained result score of 13.829. This score compared with the chi-square value in the table with dk of 14 is at the 5% significance level that is equal to 23.685, showing the results of calculation of chi square is smaller than the results of the chi square on the table (13.829 < 23.685).Key Words: Teaching Skill